RESEACH OF THREE-DIMENSIONAL CRACK GROWTH BASED ON DISK OF TURBO-SHAFT ENGINE - AI ShuMin; ZHAO ShuaiLei; ZHANG ZhiYi; DENG XiaoTao (Jixie qiangdu)
Three-dimensional crack growth was analyzed using damage tolerance design-based method and Franc3D to find cause of unexpected fatigue test failure of a turboshaft engine disk,showing that the crack propagation life was shorter than the test inspection interval which proved that damage tolerance design cannot meet the requirements and it was the major cause of the failure. Present research can provide damage tolerance design guidance for engineering application.